Standarisasi Jalan Inspeksi/Check Road Guna Meningkatkan Keamanan di Sisi Udara Bandar Udara Internasional Jenderal Ahmad Yani Semarang - Perangin Angin, Andi Frianto; Luwihono, Andung; Zaini, Faizal (Politeknik Penerbangan Jayapura, 2023)
This research aims to analyze the standardization of Check Road to improve the security on the airside of Jenderal Ahmad Yani International Airport in Semarang. The research method used is qualitative, collecting data through observations, literature review, documentation, and interviews. The results of the study reveal the need for improvement measures, including adjusting the facilities according to the established standards, expanding the coverage of perimeter patrols, and planning for the fulfillment of standards by the airport management. Based on the findings of this research, it can be concluded that standardization of the Check Road on the airside of Jenderal Ahmad Yani International Airport in Semarang is necessary to enhance security.